Pro WPF in C# 2008 Windows Presentation Foundation with .NET 3.5 - MacDonald, Matthew (Apress, 2012)
This book is an in-depth exploration of WPF for professional developers who know the .NET platform, the C# language, and the Visual Studio development environment. Previous experience with Windows Forms is useful but not required to get the most out of this book.